A study of counter-rotating impulse turbine for wave energy conversion - Effect of middle vane on the performance -. Issue 5 (March 2019) - Takao, M; Yamada, K; Sasaki, R; Alam, M M A; Okuhara, S; Kinoue, Y
Abstract: In an oscillating water column (OWC) wave energy converter, the oscillating water column caused by the sea wave motion is used to drive an air column in the air chamber. An air turbine for this bi-directional airflow is used to convert the pneumatic energy into the mechanical energy. A counter-rotating impulse turbine for wave energy conversion has been proposed by M. E. McCormick in 1978. In a previous study, authors investigated the effect of turbine geometry on the performance of the counter-rotating impulse turbine and clarified that the efficiency of the turbine is higher than a single rotor impulse turbine in a range of high flow coefficients. However, the counter-rotating impulse turbine has a disadvantage. Its efficiency in a range of low flow coefficients is remarkably lower due to the deterioration of flows between two rotors. In this study, middle vanes were installed between two rotors in order to achieve a further improvement in the performance, and its effect was investigated by using the computation fluid dynamic (CFD) analysis. As a result, it was found that the efficiency of the turbine was greatly improved by installing the middle vanes, and a favourable turbine geometry was clarified.